Therapeutic strategies for BRAF mutation in non-small cell lung cancer: a review - Puri, Megha; Gawri, Kunal; Dawar, Richa (Frontiers in Oncology, 2023)
Lung cancer is the leading cause of cancer related deaths. Among the two broad types of lung cancer, non-small cell lung cancer accounts for 85% of the cases. The study of the genetic alteration has facilitated the development of targeted therapeutic interventions. Some of the molecular alterations which are important targets for drug therapy include Kirsten rat sarcoma (KRAS), Epidermal Growth Factor Receptor (EGFR), V-RAF murine sarcoma viral oncogene homolog B (BRAF), anaplastic lymphoma kinase gene (ALK). In the setting of extensive on-going clinical trials, it is imperative to periodically review the advancements and the newer drug therapies being available. Among all mutations, BRAF mutation is common with incidence being 8% overall and 1.5 -4% in NSCLC. Here, we have summarized the BRAF mutation types and reviewed the various drug therapy available -for both V600 and nonV600 group; the mechanism of resistance to BRAF inhibitors and strategies to overcome it; the significance of comprehensive profiling of concurrent mutations, and the role of immune checkpoint inhibitor in BRAF mutated NSCLC. We have also included the currently ongoing clinical trials and recent advancements including combination therapy that would play a role in improving the overall survival and outcome of NSCLC.